Intelligent audio control in home entertainment - Li, Haiyun. (2009)
Digital audio is introducing a bold new sound in consumer audio and home theater systems. Several factors are converging to bring high-end, surround sound audio to mass market buyers: the rise of the DVD and BluRay, new formats for multichannel audio, and widespread use of digital signal processors (DSPs) in audio systems. This project looks into the exciting area of using signal processing to enhance the performance of surround speakers. This system automatically measures and corrects the acoustics of the multichannel sound system for the specific room where the system is being set up, compensating for non-ideal room acoustics, loudness of program and speaker response. The report documents the progress made by the author from August 2008 to March 2009 in fulfilling this objective. For the objective of this project, the author was more focused on automatic gain control based on the ambient noise level in the room. The gain is adjusted in the range of -12 dB to 12 dB in steps of 3 dB. The Signal-to-Noise ratio was used in the development of this application to determine the gain. Three applications were developed. The first application was the Automatic Volume Control. FFT was computed to apply weighting to the signals to obtain the loudness. This application controlled the overall volume based on the current noise and signal loudness. The second application developed was the Automatic Equalizer. The equalizer used an 8-band equalizer and the signals are analyzed by FIR band filters. Depending on the location of the noise on the frequency spectrum, the corresponding band gain was decided for the affected bands. The third application was Automatic Silent Mode. The frequency domain of the microphone input was analyzed by FFT to detect the telephone ring tongs. Once the tone is detected, the program would be turned to silent mode automatically. All the applications were developed using SDK VisualDSP++ 4.5 for Blackfin Processors. The FIR filters were designed using MATLAB’s FDATool. The applications were tested on the BF-561 EZ-KIT Lite board provided by Analog Devices.